Unsettling Ground: Arctic Urbanism on Fluid Geology - McMillan, Jason; Sheppard, Lola (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2020)
Ground is the transition across the surface and subsurface of the land, mediating environmental change and the stability of geological time. In the Canadian Arctic, dramatic seasonal cycles and warming trends are reshaping increasingly unstable ground. Inuit in communities such as Arviat, in southern Nunavut, have always dealt with geological instability using their traditional knowledge of climate and territory. However, the North has been aggressively shaped by systematic spatial interventions of resource-based economies, militarization, and administration. Federal building programs across the Territory have imposed visions of efficiency and modernity, transforming the land inhabited by Inuit into a settled ground. To “unsettle ground” is understood here as strategies to address gaps between the imposed stability and singularity of modernist, Northern master planning and housing and the richness and fluidity of the Indigenous landscape. Two trips to Arviat and extensive meetings with community members and housing advocates revealed numerous instabilities, including geological changes, adaptation of the Community Plan, and uncertain economics of public housing. Housing has failed to engage the land on a perfunctory technical level, in its ability to create a communal “social ground”, and on a larger scale the ongoing failure of community planning disregards community relationships to landscape. Conversations on the ground revealed community-centered building practices reclaiming spaces imposed by the strictures of modern colonial architecture and planning. Our research thus examines the multiple identities of ground and posits the possibility for new, respectful ways for architecture to inhabit the land in Nunavut while unsettling ground.